2014
DOI: 10.1016/j.humpath.2013.10.016
|View full text |Cite
|
Sign up to set email alerts
|

A PIK3CA mutation detected in plasma from a patient with synchronous primary breast and lung cancers

Abstract: Digital PCR is a new technology that enables detection and quantification of cancer DNA molecules from peripheral blood. Using this technique, we identified mutant PIK3CA DNA in circulating plasma tumor DNA (ptDNA) from a patient with concurrent early stage breast cancer and non-small cell lung cancer. The patient underwent successful resection of both her breast and lung cancers, and using standard Sanger sequencing the breast cancer was shown to harbor the identical PIK3CA mutation identified in peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Multiple studies have found that recurrent mutations of some cancer-related genes detected in ctDNA of plasma through ddPCR technology were promising biomarkers for early diagnosis and prognosis. 24,[34][35][36][37][38][39] Accordingly, we collected plasma of HCC patients with or without hepatic resection to detect R249S mutation in ctDNA by ddPCR. Intriguingly, we found that the presence of R249S in ctDNA was significantly associated with poor HCC prognosis, both in patients with and without surgical resection, which was consistent with the result discovered in tissue specimens.…”
Section: Tp53 R249s Mutation In Ctdna and Hcc Prognosis (Cohorts 2 mentioning
confidence: 99%
“…Multiple studies have found that recurrent mutations of some cancer-related genes detected in ctDNA of plasma through ddPCR technology were promising biomarkers for early diagnosis and prognosis. 24,[34][35][36][37][38][39] Accordingly, we collected plasma of HCC patients with or without hepatic resection to detect R249S mutation in ctDNA by ddPCR. Intriguingly, we found that the presence of R249S in ctDNA was significantly associated with poor HCC prognosis, both in patients with and without surgical resection, which was consistent with the result discovered in tissue specimens.…”
Section: Tp53 R249s Mutation In Ctdna and Hcc Prognosis (Cohorts 2 mentioning
confidence: 99%
“…Alteration in genotype may aff ect the response of patient to chemotherapy and may show a wide range of resistance [28]. Genetic variations in the PI3K-PTEN-AKT-mTOR pathway aff ect clinical outcomes in patients treated with certain types of drugs [17,29].…”
Section: Discussionmentioning
confidence: 99%
“…BEAMing (Beads, Emulsion, Amplification and Magnetics) uses emulsion PCR technology to separately amplify individual molecules and then quantify specific variants using flow cytometry. It detects somatic mutations found in ctDNA with high sensitivity (1:5000 to 1:10,000 mutants per wild type molecule) [44,45]. Using BEAMing, Higgins et al have identified mutations in the PIK3CA gene from ctDNA which were 100% concordant with tumor biopsies [46].…”
Section: Methods For Measuring Ctdnamentioning
confidence: 99%